Social Entrepreunership In Fish Farming - Ilham, Rachmad; Sudarmiatin, Sudarmiatin; Wishnu Wardana, Ludi (International Journal of Science, Technology & Management, 2023)
Entrepreneurship plays an important role in the economy as it facilitates the production of goods and services and job creation. The agriculture sector including fish farming is one of the main livelihood sources for the community and has potential for growth through entrepreneurship programs. However, there are several obstacles in achieving this goal, such as the low level of community education and knowledge as well as limited social networking access. The fishing pond farmers in Kalanganyar Village, Sedati Sub-district, Sidoarjo Regency face similar challenges with additional complexity from external barriers such as fluctuating operational costs for fish farming. This economically causes fishing pond farmers to only be able to utilize their ponds for a single source of main income and have not been able to utilize it to find alternative income sources. These challenges hinder the development of programs to improve the economic conditions of fishing pond farmers. An approach that could address these problems is social entrepreneurship focusing on increasing collaboration between fishing pond farmers and the surrounding community. Cooperation plays an important role in economic growth by facilitating business expansion. Cooperation becomes a core component in the planning and implementation process by involving fishing pond farmers and the community as active participants. The fields of cooperation need to be developed to increase the welfare of the community.